Estimates of Potential Output and the Neutral Rate for the U.S. Economy - Alichi, Ali (IMF Working Papers; Working Paper ;, 2018)
Estimates of potential output and the neutral short-term interest rate play important roles in policy making. However, such estimates are associated with significant uncertainty and subject to significant revisions. This paper extends the structural multivariate filter methodology by adding a monetary policy block, which allows estimating the neutral rate of interest for the U.S. economy. The addition of the monetary policy block further improves the reliability of the structural multivariate filter.